Complex genetic findings in a female patient with pyruvate dehydrogenase complex deficiency: Null mutations in the PDHX gene associated with unusual expression of the testis-specific PDHA2 gene in her somatic cells - Pinheiro, Ana (2020)
Human pyruvate dehydrogenase complex (PDC) catalyzes a key step in the generation of cellular energy and is composed by three catalytic elements (E1, E2, E3), one structural subunit (E3-binding protein), and specific regulatory elements, phosphatases and kinases (PDKs, PDPs). The E1α subunit exists as two isoforms encoded by different genes: PDHA1 located on Xp22.1 and expressed in somatic tissues, and the intronless PDHA2 located on chromosome 4 and only detected in human spermatocytes and spermatids. We report on a young adult female patient who has PDC deficiency associated with a compound heterozygosity in PDHX encoding the E3-binding protein. Additionally, in the patient and in all members of her immediate family, a full-length testis-specific PDHA2 mRNA and a 5′UTR-truncated PDHA1 mRNA were detected in circulating lymphocytes and cultured fibroblasts, being bothmRNAs translated into full-length PDHA2 and PDHA1 proteins, resulting in the co-existence of both PDHA isoforms in somatic cells.Moreover, we observed that DNA hypomethylation of a CpG island in the coding region of PDHA2 gene is associatedwith the somatic activation of this gene transcription in these individuals. This study represents the first natural model of the de-repression of the testis-specific PDHA2 gene in human somatic cells, and raises some questions related to the somatic activation of this gene as a potential therapeutic approach for most forms of PDC deficiency.